Large-scale seismic tests of tall concrete bridge columns with precast segmental construction. - Wang, Jui-Chen (Earthquake engineering & structural dynamics.)
Past experimental studies have shown that existing precast segmental concrete bridge columns possess unsatisfactory hysteretic energy dissipation capacity, which is an undesirable feature for applications in seismic regions. In this research, we propose new methods of precast segment construction for tall concrete bridge columns to enhance the columns' hysteretic energy dissipation capacity and lateral strength. This is accomplished by adding bonded mild steel reinforcing bars across the segment joints, strengthening the joint at the base of the column and increasing the height of the base segment (hinge segment). Four large-scale column specimens were fabricated and tested with lateral cyclic loading in the laboratory. Each specimen consisted of a foundation and 9 or 10 precast column segments. Test results of specimens with the proposed design concepts showed ductile behavior and satisfactory hysteretic energy dissipation capacity. In addition to the experimental study, an analytical study using the finite element method was conducted to understand the bond conditions, strain contours and deformation patterns of the specimens tested. Good agreement was found between the experimental observations and the results of the calibrated analytical study.